Penggunaan Rekam Medis Berbasis Komputerisasi Terhadap Pelayanan Pasien Rawat Jalan di Puskesmas Cisitu - Alriza, Repita Indah; Hidayati, Meira (Publikasi Indonesia, 2022)
Service is the process of meeting needs through the activities of others directly. Service to outpatients at the puskesmas is the main task of the medical record in charge of the registration section, to provide the best service. At the Cisitu Public Health Center already using a computerized system, the service is easier, so that patient data is automatically entered into the computer at the polyclinic he is aiming for. To find out the use of computer-based medical records for outpatient services. The research method uses data collection methods, namely field studies, field studies include direct observation or observation methods, and direct interviews with parties related to the problems studied. The results of the research are the lack of human resources and the lack of supporting infrastructure that can affect the outpatient service at the Cisitu Public Health Center which is already computerized. More attention should be paid, because if the implementation continues, there will be several obstacles, for example, there will be a buildup of patient queues and staff will be overloaded with work. It should be with the existence of a computerized system that makes the work of officers easier and the service faster.